Food Safety in the Sphere of Production and Consumption of Vegetable Products - Alekseevich Solopov, Vladimir; Alekseevich Minakov, Ivan (International Journal of Engineering and Technology, 2018)
The aim of the study is to develop theoretical provisions and practical recommendations for solving the problem of food security in the production and consumption of vegetable products. During the research, the following methods were used: statistical-economic, monographic, economic-mathematical, computational-constructive. The article considers the problem of providing the Russian population with vegetable products, especially during the off-season. The actual consumption of vegetables is 112 kg per capita per year with a rational diet of 140 kg. In the food basket of Russians, imported vegetable products occupy a significant share. Analysis of the state and trends of development of vegetable growing in the open and sheltered ground is given. For 2000-2016, the gross harvest of vegetables increased from 10.8 to 16.3 mln. tons because of higher yields while decreasing the area of vegetable crops. In vegetable production structure, production of sheltered ground occupies 9.6%. The households of the population are the main producers of vegetables. They accounted for 66.5% of the gross harvest of vegetables. The volume of vegetable production and the main directions of its increase are justified. To ensure food security, it is necessary to increase the production of vegetables and food melon crops from 18.1 to 22.5 mln. tons, including vegetables from 16.3 to 20.3 mln. tons, food melon crops – 1.8 to 2.2 mln. tons. The increase in production of vegetable products will be facilitated by improvement of state support for vegetable growing and its increase in size, its concentration in specialized farms, intensification of the industry, the revival of Russian seed production of vegetable crops, construction of modern energy-saving greenhouses and modernization of the old ones, development of agro-industrial integration.
Keywords: Russia; vegetable growing; food security; level of self-reliance; state support; specialization; intensification; agro-industrial integration.